ANALISIS DAMPAK EMBARGO MINYAK BUMI RUSIA OLEH UNI EROPA PASCA INVASI KE UKRAINA TAHUN 2022-2024 - Thussadri, Mhd Dhabit; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study focuses on the impact of the European Union's oil embargo against Russia following its invasion of Ukraine between 2022 and 2024. The embargo was part of a broader strategy of international economic sanctions, employed as a diplomatic tool to pressure Russia into ceasing its military aggression in Ukraine. As a collective of European nations that had been major importers of Russian crude oil, the European Union held a significant share of Russia’s oil export market. Consequently, the embargo exerted considerable economic pressure on the Russian economy. The research employs a qualitative descriptive method, relying on data collected through literature reviews encompassing books, academic journals, websites, and relevant official documents. This study is grounded in the theoretical framework of international political economy, with particular reference to economic sanctions theory and the nation-state level of analysis. The findings indicate that the EU’s oil embargo succeeded in economically pressuring Russia, as evidenced by a decline in its oil export revenues. However, Russia demonstrated a notable capacity for economic adaptation in response to these sanctions. The embargo also had repercussions for the European Union itself. Ultimately, the oil embargo served as a critical instrument in the West’s response to the Ukraine invasion—producing tangible economic effects, yet falling short of altering Russia's strategic decisions regarding its military actions. Keywords: Impact, Embargo, Sanctions, Economy, Crude Oil, Invasion